2020
DOI: 10.1186/s41927-019-0109-0
|View full text |Cite
|
Sign up to set email alerts
|

Successful long-term remission through tapering tocilizumab infusions: a single-center prospective study

Abstract: Background: Strategic drug therapy for rheumatoid arthritis (RA) patients with prolonged remission is not well defined. According to recent guidelines, tapering biological Disease-Modifying Anti-Rheumatic Drugs (bDMARDs) may be considered. We aimed to evaluate the effectiveness of long-term maintenance of tocilizumab (TCZ) treatment after the progressive tapering of infusions. Methods: We conducted an exploratory, prospective, single-center, open-label study, on RA patients with sustained remission of at least… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…Indeed, previous studies, such as DREAM or SONATA, were retrospective or had no control group. 24,25,33 Second, our trial proposed a progressive and DAS-driven tapering strategy, whereas the two previous studies used an abrupt discontinuation of TCZ, which could explain why the outcomes in these studies were worse than in our findings. 24 Although guidelines report that tapering of bDMARDs would be a relevant strategy in patients in sustained remission when drug tapering is considered, 12,13 our study suggests no benefit when this strategy is applied to patients receiving TCZ or ABA.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Indeed, previous studies, such as DREAM or SONATA, were retrospective or had no control group. 24,25,33 Second, our trial proposed a progressive and DAS-driven tapering strategy, whereas the two previous studies used an abrupt discontinuation of TCZ, which could explain why the outcomes in these studies were worse than in our findings. 24 Although guidelines report that tapering of bDMARDs would be a relevant strategy in patients in sustained remission when drug tapering is considered, 12,13 our study suggests no benefit when this strategy is applied to patients receiving TCZ or ABA.…”
Section: Discussioncontrasting
confidence: 57%
“…First, to our knowledge, it is the first RCT aiming to assess the possibility of tapering TCZ or ABA, for which the published data are limited. Indeed, previous studies, such as DREAM or SONATA, were retrospective or had no control group 24,25,33 . Second, our trial proposed a progressive and DAS‐driven tapering strategy, whereas the two previous studies used an abrupt discontinuation of TCZ, which could explain why the outcomes in these studies were worse than in our findings 24 .…”
Section: Discussionmentioning
confidence: 68%
“…In this context, the results of this study provide important evidence for clinical decisions on tapering TCZ dose in daily practice. A few previous studies suggested that tapering TCZ could be a feasible option, but they were single-center studies and included relatively a small number of patients ( 25 , 26 ). To the best of our knowledge, this study is the largest cohort study that investigated the efficacy of tapering TCZ in a large nationwide cohort, which strengthens the generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%